Developing a Program for Practice Management and Productivity Improvement of Infrastructure Projects by using Business Information Modeling - Khamees, Saja Abd Alrazaq; Mohammed, Sawsan Rasheed (Engineering, Technology & Applied Science Research, 2024)
The employment of Business Information Modeling (BIM) may assist the resident engineering department in reaching its long-term strategic goals. The suggested computer software was created and tested using the first package of new projects for roads, bridges, and tunnels aimed at solving the traffic congestion crisis taking place in the capital city of Iraq, Baghdad. In the context of the current study, questionnaires and personal interviews with specialists in the field of road, tunnel, and overpass construction were employed. The aim of implementing BIM is to assess the introduced program’s efficiency, verify its performance, and identify any errors, defects, or challenges that users may encounter during its application. The computer program underwent successful testing at several Resident Engineer's Offices (REOs) within the initial package of new projects aimed at addressing traffic congestion issues in Baghdad through independent verification checks. Initially, the program was utilized with the assistance of a user guide to facilitate its operation and provide a detailed description of each program feature which can provide effective decision-making and enhance REOs' computer skills.